SLC6A4 5HTTLPR Polymorphism Affects Insulin Secretion in Patients with Polycystic Ovary Syndrome - Barbara Šenk; Katja Goričar; Nika Aleksandra Kravos; Mojca Jensterle Sever; Andrej Janež; Vita Dolžan (International Journal of Endocrinology)
Purpose. To investigate in a pilot study of genetic polymorphisms in serotonin system influencing basal- and glucose-stimulated insulin secretion in women with polycystic ovary syndrome (PCOS). Methods. A cross-sectional study included 65 female patients with PCOS followed up at the endocrine outpatient clinic of the University Medical Center Ljubljana and a control group of 94 young healthy female blood donors. Oral glucose tolerance test was performed only in PCOS patients and basal- and glucose-stimulated blood glucose and insulin levels were measured. All the subjects were genotyped for 5HTR1A rs6295, 5HTR1B rs13212041, and SLC6A4 5HTTLPR polymorphisms in the serotonin system. Results. Genotype distributions were in accordance with the Hardy-Weinberg equilibrium (HWE), except for 5HTR1A rs6295 in healthy controls and 5HTR1B rs13212041 in PCOS patients that were not consistent with HWE. SLC6A4 5HTTLPR polymorphism was significantly associated with insulin secretion (p=0.030) and with the area under the curve of insulin blood levels during OGTT (p=0.021). None of the investigated polymorphisms was significantly associated with basal- or glucose-stimulated blood glucose levels at any point in time during OGTT or with the basal insulin concentration. Conclusions. Serotonin system may play a role in glucose-stimulated insulin secretion in patients with insulin resistance (IR) and decreased insulin sensitivity. Further studies are needed to conclude whether the observed effect is characteristic for PCOS-related metabolic disturbances or for the identified mutation in different high metabolic risk populations.